Real-time RSET prediction across three types of geometries and simulation training dataset: A comparative study of machine learning models - Uhlík, Ondřej; Okřinová, Petra; Tokarevskikh, Artem; Apeltauer, Tomáš; Apeltauer, Jiří (Elsevier, 2024)
Agent-based evacuation models provide useful data of the evacuation process, but they are not primarily designed for use during an emergency. The paper aims to test predicting RSET using a surrogate ML model trained on a simulation dataset with 60 samples. A total of 9 machine learning algorithms were tested on 3 simple geometries: bottleneck, stairway and walkway. A set of 7 spatial features was used to train the surrogate models. The results showed a relatively good ability of Artificial Neural Network to learn in scenarios involving bottlenecks and stairways, with an R2: 0.99 on the testing dataset. In the walkway scenario, all models experienced a significant drop in performance, with Gradient Boost performing the best (R2: 0.92). The paper demonstrated ability to generalize effectively in bottleneck-type tasks with training on a relatively small dataset containing spatial parameters obtainable in real-time from camera systems.
Keywords: Evacuation modeling; Machine learning; Required safe egress time; Agent-based models